A beginner's guide to flow kinetics. (31st March 2020) - Bagshaw, Clive R.
Abstract : For a liquid flowing through a tube at constant velocity, the distance from the point of origin can provide a measure of the reaction time. This concept of continuous flow, first applied over a century ago to follow biochemical reactions by absorption spectroscopy, is now being used in conjunction with high-resolution structural methods such as X-ray crystallography and cryo-electron microscopy. The resultant kinetic information is crucial to understanding the mechanism.